2008
DOI: 10.1111/j.1365-2133.2008.08789.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemic conditions decrease cultured keratinocyte mobility: implications for impaired wound healing in patients with diabetes

Abstract: Under hyperglycaemic conditions, keratinocytes demonstrate reduced migration and decreased proliferation capacities. These impairments of keratinocyte functions are likely to result in inadequate re-epithelialization. These defective physiological events provide a reasonable explanation for the poor wound healing commonly observed in patients with DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
125
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 90 publications
(154 reference statements)
13
125
0
1
Order By: Relevance
“…Immune dysfunctions that affect leukocyte adherence, chemotaxis and phagocytosis occur under hyperglycemic conditions and may make DM patients more prone to infections (5-7). We recently demonstrated that the physiologic functions of keratinocytes, the immune-competent cells that form the outermost layer of the skin, were also affected by high-glucose environments (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Immune dysfunctions that affect leukocyte adherence, chemotaxis and phagocytosis occur under hyperglycemic conditions and may make DM patients more prone to infections (5-7). We recently demonstrated that the physiologic functions of keratinocytes, the immune-competent cells that form the outermost layer of the skin, were also affected by high-glucose environments (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lerman et al (7) demonstrated that fibroblasts from diabetic mice migrated 75% less than those from normoglycemic mice and displayed a constant response to hypoxia, a condition commonly present in chronic wounds. Recently, an inhibition phenomenon similar to that in mice was observed in keratinocytes cultured in a high-glucose (HG) environment (8), which suggested that HG has a significant role in delaying wound repair. Mitogen-associated protein kinases (MAPKs) were identified to be involved in reactive oxygen species (ROS) production upon HG stress (9).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced keratinocyte migration is an important factor in impaired reepithelialization of chronic and diabetic healing (Stojadinovic et al, 2005;Lan et al, 2008;Usui et al, 2008;Jacobsen et al, 2010). We identified two distinct mechanisms through which FOXO1 affects keratinocyte migration, both of which are affected by diabetes in vivo and by high levels of glucose, an AGE, or TNF in vitro.…”
Section: Discussionmentioning
confidence: 97%